The Effects of Experienced, Vicarious, and Anticipated Strain on Violence and Drug Use among Inmates - Marcum, Cathy (2012)
The bulk of research on general strain theory has focused on determining the effect of experienced strain on the illegal or delinquent behaviors of juveniles or young adults. While much has been gained by this research, it is important to understand the role of experiencing and witnessing strain on adult, high risk populations (e.g., adult inmates). The current study examines the effect of experienced, vicarious, and anticipated victimization on inappropriate coping mechanisms of inmates. Specifically, it examines the effect of experiencing or witnessing physical victimization on inmates’ use of violence and drug/alcohol. Survey data from 208 adult parolees show that, at least in controlled environments like prisons, witnessing violence increases the likelihood of engaging in violence and that experiencing and witnessing violence significantly increases the likelihood that inmates will use drugs or alcohol